The affirmation of finite as a possibility for responsibilization of desire: notes from Heidegger and Lacan - Santos, Renato dos (2019)
The purpose of this paper is to demonstrate how Heidegger's claim to being-to-death can be understood as a condition of possibility for the responsibility of desire as formulated by Lacanian psychoanalysis. First, the structure of the Heideggerian Dasein, as well as its existential ones, is described. Next, the use and the sense of the notion of desire in Lacan is analyzed. Both in an authentic existence and at the end of analysis, where the subject knows how to deal with his losses, in the face of anguish, he assumes a role of protagonist of his existence and manages to be responsible for his desire. The analysis, in this sense, serves as a tool that enables the subject to deal with this suffering arising from the lack, of this nothing that Heidegger spoke. Obviously, the analysis does not aim to eliminate this ontological lack, but only to deconstruct the phantasms that the subject has constructed to ward off what is his own, constituting his ontological structure, that is, his finitude. Thus, for Heidegger, through the affirmation of anguish in the face of death, and for Lacan, where the subject has assumed the tragedy of his existence - at the end of analysis - it is the affirmation of finitude that makes it possible to hold the desire, authentic or, if you prefer, subject.